2012
DOI: 10.2217/pme.12.44
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics: Assessing Educational Exposure, Confidence in Knowledge and Training Elements of Pharmacists

Abstract: Educational program development in the format of continuing education or certificate is needed to improve pharmacists' education, confidence and training needs in PGx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…Four studies conducted in U.S revealed that pharmacists perceived themselves as the leading force for the integration of PG in to practice and also should be an important source of PG information to patients and other healthcare providers. [15][16][17]19 Similarly, one study each from UK, 9 Canada 23 and Ukraine 25 revealed same perceived roles and responsibilities towards PG among pharmacists.…”
Section: Attitudes-perceived Responsibilitiesmentioning
confidence: 81%
See 3 more Smart Citations
“…Four studies conducted in U.S revealed that pharmacists perceived themselves as the leading force for the integration of PG in to practice and also should be an important source of PG information to patients and other healthcare providers. [15][16][17]19 Similarly, one study each from UK, 9 Canada 23 and Ukraine 25 revealed same perceived roles and responsibilities towards PG among pharmacists.…”
Section: Attitudes-perceived Responsibilitiesmentioning
confidence: 81%
“…25 Three surveys were qualitative, that used one or combination of semi structure questionnaire, one-day meeting and case scenarios, 9,22,26 and with regard to design, four research were cohort study, 19,21,24,26 while the rest nine were Crosssectional studies, 9,12,15,16,18,[22][23][24][25] Pharmacogenetics or PG or pharmacogenetic testing and pharmacists or pharmacy students were discussed in all the articles. Table 1 presented the summary of included researches in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial draft of 59-item self-administered questionnaire was developed through search into the available literature and frequently ask questions (FAQs) (Adam et al, 2015a;Benzeroual et al, 2012;Filiptsova et al, 2015;Formea et al, 2013;Stanek et al, 2013;Taber and Press, 2014). An expert panel was formed in order to design flowchart and for characterizing the primary domains of our KAP survey.…”
Section: Item Generationmentioning
confidence: 99%